Carolina Currents, Studies in South Carolina Culture (University of South Carolina Press, 2026)
From the Piedmont to the Lowcountry, South Carolina is the site of countless engaging stories. The contributors to Carolina Currents share those stories, broadening our understanding of the state's unique and diverse histories and cultures. A venue for public-facing interdisciplinary scholarship, each volume presents a collection of essays that illuminates the complex interactions between the state's past and present.Essays in volume 2 cover topics including the Universities Studying Slavery project, the civil rights movement in South Carolina, and Asian immigrants in the Upstate; a review essay discusses recent work by South Carolina poets.With contributions from: Richard A. Almeida, Patti Burns, Joshua Casmir Catalano, Madison Cates, Robert M. Craig, Taylor Diggs, Jo Angela Edwins, Michael Emett, Mary Jo Fairchild, Kylie Fisher, Greg Garvan, Douglas E. Gray, Megan Hammeke, Lakin Hanna, Lynn Hanson, Christopher E. Hendricks, Landon Houle, Adam Houle, Christopher D. Johnson, Erica Johnson, Scott Kaufman, Eli Kibler, Jason Kirby, Eva Kiser, Felice Knight, Meredith A. Love, Natalie S. Mahaffey, Michael S. Martin, Jeremy D. Rentsch, Aïda Rogers, Steven Sims-Brewton, Rachel N. Spear